Antibacterial Activity of Ethanol Extract of Kersen Bark (Muntingia Calabura L) & It’s Formulation as an Anti-Acne Cream - Nanda Sabila Fitriana Putri; Siti Harnina Bintari Bintari (Universitas Negeri Semarang, 2023)
Background: Kersen (Muntinga calabura) bark is one of the medicinal plants that can be used to treat acne. The ethanol extract of kersen bark contains alkaloid, flavonoid, tannin, saponin, and terpenoid compounds that have potential as antibacterials. Objective: This study aims to make a cream preparation from ethanol extract of kersen bark and to determine the antibacterial activity against acne-causing bacteria Staphylococcus epidermidis. Methods: Extraction was done by remaceration method and 96% ethanol solvent was used to obtain the extract of kersen stem bark. Phytochemical screening was carried out to determine the secondary metabolites in the extract. The antibacterial activity test of the extract was carried out using the solid liquid dilution method to determine the KHM and KBM values. The extracts were then formulated into M/A (oil in water) cream preparations, then physically evaluated and tested for antibacterial activity using the pitting diffusion method. Results: Kersen bark contains alkaloids, flavonoids, tannins, saponins, and terpenoids that show antibacterial activity against Staphylococcus epidermidis with KHM and KBM values at a concentration of 3.125%. The physical properties of the creams showed that all creams met the requirements with 5% concentration as the minimum limit for the preparation to have antibacterial activity. Conclusion: Kersen bark extract cream formulation with the greatest antibacterial activity was obtained at a concentration of 10%, where the higher the concentration of extract used, the higher the antibacterial activity.